Diet and prevention of cardiovascular disease - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2003)
Atherosclerotic cardiovascular disease has been recognized as the leading cause of death for both men and women in developed countries. During the past century epidemiological and observational studies established that inappropriate nutrition together with reduced physical activity and increased tobacco consumption are key factors for cardiovascular disease development. Recent epidemiological and clinical trial data provide evidence of the great effectiveness of dietary interventions in cardiovascular disease prevention and treatment. Therefore, the efforts to improve diet play an important role in shifting population disease risk. In this paper, the scientific background and current recommendations for dietary prevention of cardiovascular disease are summarized.